What, How and Why Academic Writing? - Dhobi, Saleem (Historical Journal, 2024)
This paper multiple understandings of academic writing, examining the skills involved in writing, and analyzing the structure and context of scholarly writing Academic writing, also known as scholarly writing, demands a serious approach and specific skills Writers proficient in exploring ideas, analyzing information, and organizing data into a formal and comprehensible structure are better equipped to contribute to academic writing. The scientific writer emphasizes reasoning and evidence in relevant papers. The aim of this article is to inform, motivate, and educate readers about writing in general and academic writing in particular. Through qualitative analysis, this research investigates the rhetorical situation, which encompasses the writer, reader, occasion, subject, and source of information, and how these elements influence academic writing.